The ancient Romans - Lassieur, Allison (People of the ancient world, 2004)
Presents an overview of the people of ancient Rome, including information on political organization, scholars, philosophers, writers, soldiers, women, priests, architects, the working-class, and slaves. Includes index and glossary.